Peran Orang Tua dalam Kesejahterahan Sosial-Emosional Anak dengan Penyakit Kronis : Studi Kasus di Sentra “Budi Perkasa” Palembang - Imam Al Jundi; Nurlela, Nurlela; Evia Darmawani (Yayasan Literasi Sains Indonesia, 2024)
This research aims to investigate the role of parents in the social-emotional well-being of children with chronic illnesses in Sentra Budi Perkasa Palembang. Descriptive qualitative and case study methods were used to gain an in-depth understanding of the influence of parents on child development. Through data triangulation techniques (observation, interviews, and documentation), this study identified several critical aspects, including understanding and appreciation of the child, support for emotional development, combating stigma, and efforts to improve the child's social well-being. The results of the study show the complexity of challenges faced by parents, ranging from the complexity of health problems to a lack of readiness in dealing with medical aspects. Parents also play an important role in overcoming societal stigma and helping children develop healthy social-emotional skills. In conclusion, this research provides in-depth insights into the role of parents in supporting children with chronic illnesses, highlighting the need for comprehensive support, collaboration with healthcare teams, and joint efforts to create an environment that supports holistic child development.